2004
DOI: 10.1093/intimm/dxh053
|View full text |Cite
|
Sign up to set email alerts
|

Natural human polyreactive IgM induce apoptosis of lymphoid cell lines and human peripheral blood mononuclear cells

Abstract: Natural polyreactive IgM autoantibodies, encoded by unmutated germline Ig V genes, represent a major fraction of the normal circulating IgM repertoire. We have previously shown that therapeutic preparation of pooled IgM exerts immunomodulatory effects as assessed by in vitro and in vivo studies. Here, we show that the IgM preparation induces cell death in lymphoblastoid cell lines and in human peripheral blood mononuclear cells. The IgM-induced cell death involved classical features of apoptosis such as nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 64 publications
2
28
0
2
Order By: Relevance
“…75,76 Clinical and experimental data support a potential role of complement in the control of neoplastic cells. In cancer patients, endogenous complement activation has been demonstrated with subsequent deposition of complement components on tumor tissue.…”
Section: Mechanisms Of Cell Lysismentioning
confidence: 96%
“…75,76 Clinical and experimental data support a potential role of complement in the control of neoplastic cells. In cancer patients, endogenous complement activation has been demonstrated with subsequent deposition of complement components on tumor tissue.…”
Section: Mechanisms Of Cell Lysismentioning
confidence: 96%
“…The IgM-induced cell death involved classic features of apoptosis, such as nuclear fragmentation and activation of caspases (14). Soluble Fas molecules inhibited this natural autoantibody-induced apoptosis, suggesting that the Fas pathway is involved.…”
Section: Natural Autoantibodies As Protective Immunoglobulinsmentioning
confidence: 96%
“…Nef. Recently, it has been reported that in preparation of the natural IgM fraction, antibodies reactive with Fas were shown to have the capacity to induce apoptosis of lymphoblastoid cells (19). On the other hand, 2G9 reacted with HIV-1-infected cells, in which Fas expression is downregulated indicating that it does not react with Fas.…”
Section: Discussionmentioning
confidence: 99%